Discovery of SIP/DRIP approach in distributed inter process communication - Hamid H.; Jais J. (2023)
Classification modeling in data mining has evolved since 1990's. Many methods have been introduced and experimented. Among them were Multi Layer Perceptron and Radial Basis Function in Neural Network and Multiple Regressions in Statistical Analysis. Not many researches have been proposed in the field of rough classification modeling. When SIP/DRIP algorithm was ported on rough classification model, its accuracy has shown competitive results [1]. The performance of the proposed rough model is compared with neural classifiers on different datasets. This paper made experiments on the combination of SIP/DRIP algorithm with DIPC distributed system to increase the computation speed of the method. Comparison made with another distributed computing system will be presented. 2008 IEEE.